Outcomes after cervical laminectomy with instrumented fusion versus expansile laminoplasty: A propensity matched study of 3185 patients. Issue 3 (March 2015) - Adogwa, Owoicho; Huang, Kevin; Hazzard, Matthew; Chagoya, Gustavo; Owens, Ryan; Cheng, Joseph; Ugiliweneza, Beatrice; Boakye, Maxwell; Lad, Shivanand P.
Abstract The aim of this study was to compare reoperation, complication rates, and healthcare resource utilization of expansile laminectomies with instrumented fusion versus laminoplasty. Using the MarketScan database (Truven Health Analytics, Ann Arbor, MI, USA), we selected patients aged >18 years who underwent either cervical laminoplasty or laminectomy with fusion between 2000–2009. Propensity score modeling produced a matched cohort balanced for age, sex, comorbidities, and other relevant factors. A total of 3185 patients meeting our inclusion criteria also had 2 year follow-up available. Of these, 2927 (91.90%) and 258 (8.10%) had laminectomy with fusion and laminoplasty, respectively. Laminoplasty patients had significantly lower complication rates during index hospitalization (5.81 versus 9.62%, adjusted odds ratio [aOR]: 0.556, 95% confidence interval [CI]: 0.418–0.740, p < 0.0002), during 30 day (6.87 versus 11.12%, aOR: 0.568, 95% CI: 0.436–0.740, p < 0.0002) and 90 day (7.61 versus 11.78%, aOR: 0.593, 95% CI: 0.460–0.764, p < 0.0002) postoperative periods. They also had lower costs (United States dollars) during index hospitalization ($26, 129 versus $35, 483, p < 0.0004), and overall during the 2 year postoperative period ($77, 960 versus $106, 453, p < 0.0001). Two year reoperation rates were similar between both groups (9.77% versus 7.36%, p = 0.20). Our study suggests that cervical laminoplasty has significantly lower complication rates, similar long-term reoperation rates and lower healthcare resource utilization after 2 years than laminectomy with fusion.